Improving population estimates of Swedish birds using the Breeding Bird Survey fixed routes and correction factors from Finnish line transect surveys - Svensson, Sören (Ornis Svecica, 2016)
I estimated population size of fifty-nine common birds by using the fixed routes of the Swedish Bird Survey (SBS), which give the number of birds per kilometer. I converted this number to density, birds/km2, using the correction factors for detectability that have been developed for line transects in Finland. I compared the population estimates by this new method with those in a previous account from 2012, in which the estimates of common birds were primarily based on extrapolation of habitat-specific densities from numerous territory mapping plots. There was good agreement for the most abundant species but a clear tendency that the estimates with the new method were higher for many less common ones. As little new density data are being collected, the SBS fixed routes are likely to be the prime source of data for future national population estimates. Although the Finnish correction factors can be used to improve the Swedish estimates for suitable species it is advisable to develop factors specifically adapted to the Swedish counts for application to a wider spectrum of species.